Erythrocytes as a preferential target of oxidative stress in blood. (4th May 2021) - Fujii, Junichi; Homma, Takujiro; Kobayashi, Sho; Warang, Prashant; Madkaikar, Manisha; Mukherjee, Malay B.
Abstract: Red blood cells (RBC) are specifically differentiated to transport oxygen and carbon dioxide in the blood and they lack most organelles, including mitochondria. The autoxidation of hemoglobin constitutes a major source of reactive oxygen species (ROS). Nitric oxide, which is produced by endothelial nitric oxide synthase (NOS3) or via the hemoglobin-mediated conversion of nitrite, interacts with ROS and results in the production of reactive nitrogen oxide species. Herein we present an overview of anemic diseases that are closely related to oxidative damage. Because the compensation of proteins by means of gene expression does not proceed in enucleated cells, antioxidative and redox systems play more important roles in maintaining the homeostasis of RBC against oxidative insult compared to ordinary cells. Defects in hemoglobin and enzymes that are involved in energy production and redox reactions largely trigger oxidative damage to RBC. The results of studies using genetically modified mice suggest that antioxidative enzymes, notably superoxide dismutase 1 and peroxiredoxin 2, play essential roles in coping with oxidative damage in erythroid cells, and their absence limits erythropoiesis, the life-span of RBC and consequently results in the development of anemia. The degeneration of the machinery involved in the proteolytic removal of damaged proteins appears to be associated with hemolytic events. The ubiquitin-proteasome system is the dominant machinery, not only for the proteolytic removal of damaged proteins in erythroid cells but also for the development of erythropoiesis. Hence, despite the fact that it is less abundant in RBC compared to ordinary cells, the aberrant ubiquitin-proteasome system may be associated with the development of anemic diseases via the accumulation of damaged proteins, as typified in sickle cell disease, and impaired erythropoiesis.